Serum proinflammatory cytokines, receptor activator of nuclear factor kappa-Β ligand (RANKL), osteoprotegerin (OPG) and RANKL/OPG ratio in mild and severe COVID-19 - Siamak Kazemi-Sufi; Shahriar Alipour; Masome Rabieepour; Shiva Roshan-Milani; Roya Naderi (BMC Infectious Diseases, 2024)
Abstract Introduction Osteoporosis, a systemic skeletal disease, is characterized by a quantitative and qualitative, and progressive decrease in bone mass, which is related to inflammation. Since a cytokine storm is triggered in Coronavirus disease 2019 (COVID-19), this study aims to evaluate pro-inflammatory cytokines (TNF-α, IL-1β), Receptor activator of nuclear factor-κB ligand (RANKL)/serum osteoprotegerin (OPG) ratio, and their relationship in mild and severe COVID-19. Methods This study was performed on 48 adult patients (18 mild, 18 severe COVID-19, and 12 healthy subjects as a control group). Serum OPG, RANKL, TNF-α, IL-1β, 25-OH vitamin D, and ALKp were measured by ELISA and colorimetric assay. Results COVID-19 patients had a significant increase in RANKL, and RANKL/OPG in mild and severe form (p < 0.001) while OPG decreased significantly in severe form compared to healthy controls (p < 0.05). Inflammatory cytokines (TNF-α and IL-1β) increased in both groups of patients whereas Alkaline phosphatase (ALKp) increased only in severe patients (p < 0.001). Both groups had 25-OH vitamin D deficiency in comparison to healthy ones (p < 0.001). Pearson’s correlation coefficient was performed to determine the relationship between RANKL, OPG, ALKp, and 25-OH vitamin D with TNF-α and IL-1β in mild and severe COVID-19, which was statistically significant. Conclusion Serum RANKL/OPG ratio was elevated in COVID-19 individuals and is assumed to be a risk factor for BMD reduction and osteoporosis in these patients. Correlations between IL-1β, TNF-α, ALKp, 25-OH vitamin D, OPG, RANKL, and RANKL/OPG ratio offered the potential role of these proinflammatory markers in the mechanism of osteoporosis in COVID-19 patients.